Edible coatings used for conservation of minimally processed vegetables: a review (Research, Society and Development, 2020)
The minimally processed vegetable (MPV) market has been growing in recent decades. This growth is related to the change in lifestyle and eating habits of consumers who seek practical and healthy food for consumption. Maintaining the characteristics and quality of MPVs is a significant challenge for producers and traders. Minimal processing steps increase the perishability of these MPVs, thus increasing oxidative reactions and their metabolic rate. The research focused on the development of technologies that reduce these reactions gained prominence. Edible films and coatings produced from natural sources have emerged as alternative packaging for food applications and have received attention due to their advantages, such as their biodegradable and renewable nature, availability, and cost. The use of edible coatings for the preservation of vegetables in the postharvest condition, whether intact or minimally processed, has been identified as an emerging technology of great potential as they can control the internal atmosphere of MPVs. Biopolymers such as polysaccharides, lipids, and proteins have been evaluated in the formulation of these coatings. The choice of appropriate material will depend on the characteristics of the plant, the biopolymer, and the intended objectives of the film. This review aims to present some application examples, the main types of edible coatings, and the application techniques used in MPVs based on the literature, to assist a choice that can generate greater coating efficiency.